Signal peptidase 21 suppresses cell proliferation, migration, and invasion via the PTEN-PI3K/Akt signaling pathway in lung adenocarcinoma - Zhang, Na; Cao, Shiguang; Sun, Ruiying; Wang, Yibei; Liu, Luna; Wang, Wei; Meng, Xia (PeerJ, 2022)
Background In a previous study, a total of 568 differentially expressed proteins including the signal peptidase SPC21 were identified from lung adenocarcinoma (LUAD) and paired normal lung tissues. In this study, the role of SPC21 in LUAD progression was investigated. Methods The relationships and protein-protein interaction network of proteins differentially expressed between paired LUAD samples and adjacent normal tissues samples were identified via the String and Pajek software, respectively. The expression levels of the hub protein SPC21 were analyzed in 84 LUAD-normal paired tissues via immunohistochemistry. The prognostic value of SPC21 mRNA was investigated in 478 LUAD patients from TCGA and GTEx datasets. siRNAs were used in A549 and NCI-H1299 cells to knockdown SPC21. The SPC21 biological function was evaluated using the CCK-8, EdU, plate colony formation, transwell, wound healing, and adhesion assays. Results Patients with lower SPC21 mRNA levels tended to have worse prognosis (overall survival) than those with higher mRNA levels. SPC21 expression was significantly downregulated in LUAD tumor tissues compared with that in paired normal tissues (P < 0.001). Functionally, SPC21 knockdown promoted cell growth, migration, and invasion. Further analyses showed that SPC21 inactivated Akt signaling, and the Akt inhibitor MK-2206 blocked the tumor-promoting effects of SPC21 knockdown. Conclusions SPC21 plays a tumor suppressor role in LUAD cells by targeting the PTEN-PI3K/Akt axis and might be used as a prognostic indicator and therapeutic target in LUAD patients.
Keywords: SPC21; Lung adenocarcinoma; Akt; PTEN